Investigation of seedling-stage salinity tolerance QTLs using backcross lines derived from Oryza sativa L. Pokkali - Alam, Rebjana; Sazzadur Rahman, M.; Seraj, Zeba I.; Thomson, Michael J.; Ismail, Abdelbagi M.; Tumimbang-Raiz, Ellen; Gregorio, Glenn B. (Wiley, 2011)
With 2 figures and 5 tables A population of BC3F4 rice lines derived from a cross of salt‐tolerant Pokkali and sensitive IR29 was developed for validation of the Saltol QTL and comparison of this QTL effect with background QTLs. Specific BC3F4 progenies from the advanced backcross population were found to have similar salinity tolerance at the seedling stage even without the Saltol alleles. Therefore, additional QTLs responsible for seedling‐stage salinity tolerance were investigated by screening and genotyping with markers at multiple loci throughout the 12 rice chromosomes. Single marker regression (SMR) using Q‐Gene detected seven QTLs above the threshold logarithm of the odds of 3.0. Single marker analysis using IciMapping detected the same markers linked to the seven QTLs identified by SMR. Likelihood ratio test‐based on stepwise regression (LRT‐RSTEP) analysis using IciMapping, more suitable for BC3F4 introgression lines located six QTLs, of which two were common with SMR and included two significant segments within Saltol. The new non‐Saltol QTLs represent targets for further study to evaluate their usefulness in breeding for higher levels of seedling‐stage salinity tolerance in rice.